1985
DOI: 10.2307/1380919
|View full text |Cite
|
Sign up to set email alerts
|

Food Habits of Cave-Dwelling Bats in the Central Appalachians

Abstract: The food habits of four species of cave-dwelling bats, Eptesicus fuscus, Myotis keenii, M. lucifugus, and Pipistrellus subflavus, were investigated in the central Appalachians. Information was based primarily on analysis of fecal pellets; however, some stomachs also were examined for food items for comparison with the first procedure. Coleopterans and hemipterans occurred in more than 70% of the adult male E. fuscus samples. All of the hemipterans were green stink bugs, Acrosternum hilare. More than 50% of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
23
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 25 publications
7
23
1
Order By: Relevance
“…Fecal analysis showed Lepidoptera to be the most common element in the diet, which may suggest that this bat forages for prey opportunistically. However, although beetle-eating is common amongst many different species of insectivorous bats (e.g., Freeman, 1979;Griffith and Gates, 1985;Warner, 1985;Zubaid, 1988), we found that T. mela no pogon consumed hemipteran and dipteran insects disproportionately more, and Coleptera disproportionately less, than expected based on our lighttrapping results. This result suggests that T. me lanopogon may be a somewhat selective or specialized feeder.…”
Section: Dietcontrasting
confidence: 66%
“…Fecal analysis showed Lepidoptera to be the most common element in the diet, which may suggest that this bat forages for prey opportunistically. However, although beetle-eating is common amongst many different species of insectivorous bats (e.g., Freeman, 1979;Griffith and Gates, 1985;Warner, 1985;Zubaid, 1988), we found that T. mela no pogon consumed hemipteran and dipteran insects disproportionately more, and Coleptera disproportionately less, than expected based on our lighttrapping results. This result suggests that T. me lanopogon may be a somewhat selective or specialized feeder.…”
Section: Dietcontrasting
confidence: 66%
“…Visual estimation of volume has been the most commonly used method to quantify diet (Moosman et al 2012) and it was used to facilitate comparison with the greatest number of studies (Whitaker 1972;Whitaker et al 1981;Griffith and Gates 1985;Whitaker and Lawhead 1992;Whitaker 1995;Agosta and Morton 2003;Carter et al 2003;Whitaker 2004;Whitaker and Barnard 2005;Johnson and Gates 2007;Moosman et al 2007;Feldhamer et al 2009). …”
Section: Sample Analysis and Prey Identificationmentioning
confidence: 99%
“…Most authors have defined guild structure according to differential prey utilization (Whitaker 1972;Kunz 1973;Black 1974;Whitaker et al 1981;Griffith and Gates 1985;Warner 1985;Carter et al 2003;Whitaker 2004;and Feldhamer et al 2009). However, comparing results across studies is difficult because of variation in both bat diet and study methodology.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have examined diets of insectivorous bats in North America (e.g., Whitaker and Tomich, 1983;Belwood and Fullard, 1984;Brack and LaVal, 1985;Griffith and Gates, 1985;Warner, 1985;Dalton et al, 1986), but feeding habits of several species have not been described. Confirmation of the feeding habits of C. t. ingens could not only add more insight to the allotonic frequency hypothesis but also enhance conservation of this endangered North American bat (U.S. Fish and Wildlife Service, 1995).…”
Section: Introductionmentioning
confidence: 99%